IDENTIFIKASI KULTIVAR LOKAL PADI SAWAH (Oryza Sativa L) KALIMANTAN TIMUR BERDASARKAN KARAKTER AGRONOMI DAN MORFOLOGI - Rusdiansyah -; Yazid Ismi Intara (Agrovigor, 2015)
The objective of this researchis identification local low land rice cultivars explored based on morphological and agronomical character from East Kalimantan. This research used single plot and single plant method. The data were then analyzed by computerized Cluster Analysis. Research result showed identification stalk and plant heightwas found that most cultivar were medium height ( 130 cm), medium stalk diameter (5-7 mm), large amount of tillerand productive tiller ( 25 tillers). Identification on morphological character or traits of ligule and leaf showed that all cultivars had colorless or white and split-shaped ligules, light green collars, and light green auricles. Most of them had ligules of medium length ( 20 mm), leaves of medium length ( 61-80 cm), narrow leaf width (1-2 cm), smooth leaf surface, and green colored leaves.The results of identification on morphological traits of panicle and grain showed that any cultivar have axis of panicle floppy and that a greater part of the cultivars had long panicles (25 cm), compact and straggle or dense panicles, relatively large amount of secondary branches, panicle position is a little above the flag leaf, rice grain most of which were tilled with yellow strawcolor, stigma of rice with yellow strawcolor, head pistil with white color, palea lemma with yellow strawcolor, lemma sterile turn yellow straw color with sterile length of lemma in short criterion.The result of cluster analysis combination of all existing traits or character indicated that 26 local low land rice cultivar of East Kalimantan identified there were not found cultivarsof 100 % similar.Keywords: identification, local cultivar, low land rice, Agronomy, Morphology